Family member reported symptom burden, predictors of caregiver burden and treatment effects in a goal-oriented community-based randomized controlled trial in the chronic phase of traumatic brain injury - Marianne Løvstad; Ida Maria Henriksen Borgen; Solveig Lægreid Hauger; Ingerid Kleffelgård; Cathrine Brunborg; Cecilie Røe; Helene Lundgaard Søberg; Marit Vindal Forslund (BMC Neurology, 2024)
Abstract Background Family members are often affected by the long-term consequences of traumatic brain injury, but are rarely involved in rehabilitation programs in the chronic phase. We thus do not know what family members´ main concerns are in the chronic phase, what factors are associated with perceived caregiver burden, and whether family members´ health and functioning improves due to rehabilitation efforts received by the patients. This study explored family-members` functioning, predictors of caregiver burden and effect for family members of a goal-oriented intervention in the chronic phase of traumatic brain injury. Methods Family members self-reported data measuring their caregiver burden, depression, general health, loneliness, and their evaluation of patient competency in everyday life, patient awareness levels, main problem areas (target outcomes) for the patient related to the brain injury, and demographic data were collected. Regression models were used to explore predictors of caregiver burden, and mixed models analysis was used to explore treatment effects. Results In total, 73 family members were included, 39 in the intervention group and 34 in the control group. Moderate to high caregiver burden was reported by 40% of family members, and 16% experienced clinical levels of depression. Family member loneliness and their evaluation of the patient`s level of functional competency explained 57% of the variability in caregiver burden. There were no treatment-related changes in caregiver burden, family member depression or general health. At T2 there was however a significant reduction in how family members rated severity of target outcomes that the family members had nominated at baseline (-0.38, 95% CI, -0.75 to -0.02, p = 0.04), but not for the target outcomes the patients had nominated. Conclusions A significant proportion of family members to patients in the chronic phase of TBI continue to experience challenging caregiver burden and emotional symptoms. Both family member-related and patient factors contribute to caregiver burden. Interventions targeting patient complaints do not automatically alleviate family members´ burden. It is important to address social support for family members early after injury, and there is a need for more interventions specifically targeting family members´ needs. Trial registration The trial was registered at ClinicalTrials.gov, NCT03545594 on the 4th of June 2018.